KOMENTAR DAN EMOSI PARA GAMERS TENTANG GAME VALORANT DALAM PERBINCANGAN DI SERVER DISCORD TOMB HUNTER - Fitri, Karina Dwi; tanti, dewi sad (Reputasi : Jurnal Public Relations, 2025)
This research is titled Comments and Emotions of Gamers About the Game Valorant Discussed in the Tomb Hunter Discord Server. The purpose of this study is to analyze the dynamics of discussions in the Tomb Hunter community on the Discord platform regarding the game Valorant, with a focus on discussion themes, emotional distribution, interactions, and the meanings constructed. The research problem addressed is how community members discuss, express emotions, and interact with one another. The research method used is Netnography with qualitative content analysis. The data is analyzed using the software Orange for visualizing emotional distribution and Word Cloud, and Gephi for mapping communication interactions. The findings show that discussions are divided into two main themes: competitive experiences related to the ranked game mode and social activities such as invitations to play together. Positive emotions, such as happiness and enthusiasm, dominate, particularly in relation to achievements in the game and new feature updates. However, negative emotions like frustration and anger also arise, especially related to technical issues and in-game challenges. Interactions reveal the presence of central accounts that facilitate discussions, as well as the formation of clusters based on themes such as gameplay strategies and technical problems. This research provides insights into communication dynamics within digital communities, particularly among Valorant players.